Effects of 8 week step-aerobic exercises on (state and trait) anxiety levels and quality of life of women - Duygu Sevınc; Mergul Colak; Necip Kıshalı (Türk Spor ve Egzersiz Dergisi)
The aim of this paper is to compare and determine anxiety levels and quality of life of women doing regular 8-week step-aerobic exercise and who didn't and to examine the effects of exercises on these parameters. Ninety six voluntary people, 48 in experimental group and 48 in control group, took part in the study. Average age, height, weight of the women comprising experimental and control groups, are 27.23 ± 9.02 years, 164.4627.23 ± 5.31 cm, 70.63±12.35 kg and 32.94 ±9.12 years, 164.56 ±6.36 cm, 65.33 ± 9.55, respectively. The women in the experimental group did moderately (KAH MAX. 40-60 %) step-aerobic and pilates exercises 3 days a week for 75 minutes for 8 weeks. To determine trait and state anxiety levels of each individual who participated in the study, State (STAI FORM TX -I ) and Trait (STAI FORM TX -2 ) Anxiety Inventory developed by Spielberger et al. and whose reliability and validity analysis was conducted by Öner and Le Coumpte was administered. To assess life quality of participants, SF-36 scale was used, which was developed by Ware and whose reliability and validity analysis was completed by Kocyigit et al. Following 8 week exercise program, significant positive changes were observed (p lt;0.01) in the trait anxiety and life quality level of the experimental group except state anxiety level and bodily pain state, which is one of the physical health condition subscales. In the control group, no significant changes were found in any indicator except in general health status and total physical health scores, indicators of quality of life.  Compared to the control group, in the experimental group 8 week exercise program used in this study had a positive effect on trait anxiety levels and life quality of women at this age.